Shared Value Potential of Transporting Cargo via Hyperloop - Werner, Max; Eissing, Klaus; Langton, Sebastian (Frontiers in Built Environment, 2016)
This research estimates the shared value created by constructing a hypothetical Hyperloop to transport cargo along 300 km in Northern Germany. Following Porter-Kramer (2011), we identified and evaluated eight factors that create shared value: travel speed, operating costs, safety, noise pollution, air pollution, climate effect/carbon footprint, separation effect/ property efficiency, and maintenance. Using official data compiled by several German institutes and organizations, we conducted comparative analysis to quantify and compare the abovementioned factors for Hyperloop and over-the-road cargo transport in Germany. Then, we monetized the individual and collective benefits of the shared value created by Hyperloop replacing a significant share of cargo transported by truck. Our findings indicate that the hypothetical Hyperloop project in Northern Germany would create €660 to €900 million of shared value annually. Our research method establishes a framework for assessing future transportation projects like Hyperloop, and our findings can be generalized to industrialized nations beyond Germany.